2011
DOI: 10.1386/cjcs.3.1.95_7
|View full text |Cite
|
Sign up to set email alerts
|

Mapping communication research in Catalonia: A comparative analysis of publication patterns in scholarly journals (20072009)

Abstract: The article analyses the main characteristics of scientific production in the communication sciences by Catalan authors during the years 20072009. Bibliometric techniques were used to observe institutional productivity, publication patterns, collaboration dynamics (intra- and inter-institutional) and journal consumption. The study is based on articles by authors attached to Catalan universities, companies and institutions and published in any of the sixteen main Spanish communication journals or in publicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 1 publication
0
3
0
4
Order By: Relevance
“…Here, scholars have not only expanded focus to a variety of topics but have used bibliometrics to examine communication research in different geographical regions. For instance, Masip and Fernández-Quijada (2011) found that authors in Catalonia, Spain, were more likely to collaborate when publishing in international journals than when publishing in local journals. The authors explained this to be the result of the low levels of participation among Spanish scholars in international journals.…”
Section: Citation Analysis In Communication Researchmentioning
confidence: 99%
“…Here, scholars have not only expanded focus to a variety of topics but have used bibliometrics to examine communication research in different geographical regions. For instance, Masip and Fernández-Quijada (2011) found that authors in Catalonia, Spain, were more likely to collaborate when publishing in international journals than when publishing in local journals. The authors explained this to be the result of the low levels of participation among Spanish scholars in international journals.…”
Section: Citation Analysis In Communication Researchmentioning
confidence: 99%
“…To complement the results found here, further research should be conducted to investigate other equally important contributing factors, such as possible differences in internationally and nationally published research -as illustrated by the Catalan case (Masip and Fernández-Quijada (2011) -the own perceptions of Nordic researchersthrough qualitative research -or an examination of areas in which a common Nordic approach would make sense. Note 1.…”
Section: Discussionmentioning
confidence: 96%
“…Respecto a los patrones de colaboración más frecuente, las coautorías en España, tanto en Ciencias Sociales (Olmeda- Gómez et al, 2009) como en Comunicación Fernández-Quijada, 2011), están marcadas por la proximidad geográfica, de modo que las relaciones responden a las divisiones geopolíticas (comunidades autónomas) propias del estado español.…”
Section: Estado De La Cuestiónunclassified
“…Metodológicamente, y referido siempre de manera específica al área de Comunicación en España y Latinoamérica, aunque el análisis de redes sociales se ha empleado para analizar la coautoría en escenarios locales como el catalán Fernández-Quijada, 2011), generalmente el método se ha aplicado a tesis doctorales y no a artículos científicos (Repiso; Torres-Salinas; Delgado-López-Cózar, 2011; Casanueva-Rocha; Caro-González, 2013).…”
Section: Justificación Y Novedadunclassified